Discrete Element Modeling of Rock Materials with Dilated Polyhedral Elements. (2015) - Ji, Shunying; Sun, Shanshan; Yan, Ying
Abstract: Considering the irregular shapes of rock particles, a three dimensional dilated polyhedral element is generated with the Minkowski Sums operator. This dilated element can also be constructed with a basic sphere and real polyhedron based on the theory of Minkowski Sums. The element generation, contact resolution and detection are introduced in this paper. All inter-element contacts are grouped as three categories: edge-edge, vertex-surface, and surface -surface. This dilated polyhedral element is applied to simulate the dynamic behaviours of rock rubbles of railway ballast. The settlement and the bulk stiffness of ballast are analyzed under cyclic loading. The ballast particles are mixed randomly with initial dense packing. The results showed that permanent deformation increased with the loading frequency and number of loading cycle. The influence of inter-element friction is tested in the DEM simulations. In the next study of dilated polyhedral elements, the parallel algorithm of GPU technique will be developed to improve the computational efficiency.